Infringement of Copyright Laws on Books and Documents - Lauwda, Billy; Gemilang, Daniel Putra; Ferguson, Jessica Dara (Anthology: Inside Intellectual Property Rights, 2023)
Copyright is a legal concept that provides creators with exclusive rights to their original works, including the right to reproduce, distribute, and create derivative works based on their original works. However, systems for protecting unpublished works remain fragmented internationally. Primary copyright infringement occurs when a person directly infringes on the copyright holder's exclusive rights, while secondary copyright infringement involves contributing to or facilitating the primary infringement of a copyrighted work by someone else. The debate over the balance between the protection of intellectual property and the public's right to access and share information continues to be an important issue in the development of copyright law. In our paper we will be assessing the legal workings of Copyright and analysing cases in regards to Copyright to further explain on the concept.